The Promising Therapeutic Effects of Nigella Sativa - Rimenda Sitepu; Kirsten Putriani Hartman; Yessy Adhi Utami (MEDICINUS, 2021)
Medicinal plants can be potential source to improve general health and perhaps for the treatment of various diseases. However, despite the fact that herbal medicine has been used among various civilizations worldwide, scientific research regarding many herbal medicines was still limited. Nigella sativa (N. sativa), commonly known as fennel flower, black caraway, black cumin, jintan hitam, or kalonji, is a widely used medicinal plant that has been used for the treatment of various health problems. N. sativa contains some compounds that are potentially beneficial for health and wellness, particularly thymoquinone (TQ). Studies have shown some therapeutic benefits of N. sativa, however most them require further investigations to evaluate its efficacy and safety profile. This paper provides summary of available studies and reviews of N. sativa, including findings and limitations of the studies.